2000
DOI: 10.1161/01.res.87.6.460
|View full text |Cite
|
Sign up to set email alerts
|

Opening of Mitochondrial K ATP Channels Triggers the Preconditioned State by Generating Free Radicals

Abstract: Abstract-The critical time for opening mitochondrial (mito) K ATP channels, putative end effectors of ischemic preconditioning (PC), was examined. In isolated rabbit hearts 29Ϯ3% of risk zone infarcted after 30 minutes of regional ischemia. Ischemic PC or 5-minute exposure to 10 mol/L diazoxide, a mito K ATP channel opener, reduced infarction to 3Ϯ1% and 8Ϯ1%, respectively. The mito K ATP channel closer 5-hydroxydecanoate (200 mol/L), bracketing either 5-minute PC ischemia or diazoxide infusion, blocked protec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
446
7
31

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 613 publications
(506 citation statements)
references
References 39 publications
22
446
7
31
Order By: Relevance
“…A pivotal cardioprotective role for NO • from enzymatic and non-enzymatic origin has been shown for both pre and postconditioning [13,15,25,26,[46][47][48][49][50]60,66,69]. In fact, NO • is a cardiovascular protective molecule via multiple effects, both in normoxia and particularly during reperfusion [15,50,66].…”
Section: Early Reperfusionmentioning
confidence: 99%
See 1 more Smart Citation
“…A pivotal cardioprotective role for NO • from enzymatic and non-enzymatic origin has been shown for both pre and postconditioning [13,15,25,26,[46][47][48][49][50]60,66,69]. In fact, NO • is a cardiovascular protective molecule via multiple effects, both in normoxia and particularly during reperfusion [15,50,66].…”
Section: Early Reperfusionmentioning
confidence: 99%
“…Both in vivo and in vitro ischemic-and pharmacologicalpreconditioning triggering require protective ROS signaling. In fact, either ROS-generators or ROS-scavengers, given before the index ischemia, trigger or abolish preconditioning [2,7,10,16,23,43,47,48,61]. Therefore, ROS are double edge swords (ROS stress vs ROS signaling).…”
Section: Introductionmentioning
confidence: 99%
“…The release of oxygen free radicals (OFR) is a cause of myocardial lesion during post-ischemia reperfusion. Paradoxically, Pain et al [9] and Forbes et al [10] showed that the release of reactive oxygen species (ROS) participates in the protective mechanism of the IP by opening of mitoK + ATP channels and activation of kinases. N-acetylcysteine is classified as an antioxidant, but has broad clinical utility as a mucolitic agent, as antidote for acetaminophen poisoning, prevention of renal dysfunction by use of radiocontrasts and potentiator of hemodynamic effects of nitroglycerin.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [12] noted that N-acetylcysteine blocked the loss of glutathione and the protective effect of IP, but its protocol with four cycles of 5 minutes of ischemia and reperfusion resulted in myocardial stunning before the sustained period of ischemia. Pain et al [9] proposed that the OFR had a paradoxical role in the protection provided by IP, encouraging us to study the effects of antioxidant Nacetylcysteine on the mechanism of IP in isolated rat hearts according Langendorff model. N-acetylcysteine has wide clinical use, and is used in many patients undergoing heart surgery.…”
mentioning
confidence: 99%
“…Furthermore, the results obtained with 5-HD were confirmed with glibenclamide, which acts as a general inhibitor of KATP channels. It has already shown that opening of mitoKATP channels is followed by an increase in ROS generation, and that this is reduced after blocking the channels with 5-HD or glibenclamide (Pain et al, 2000;Krenz et al, 2002;Andrukhiv et al, 2006).…”
Section: Discussionmentioning
confidence: 98%